ANALISIS RETURN ON INVESTMENT DAN RESIDUAL INCOME UNTUK MENILAI KINERJA KEUANGAN PT. BIRINGKASSI RAYA KABUPATEN PANGKEP - Sri Wahyuni Nur (Distribusi - Journal of Management and Business, 2022)
This study aims to determine the company's financial performance by using Return on Investment and Residual Income. The object of this research is PT. Biringkassi Raya is located in Pangkep Regency, South Sulawesi Province. The type of data used in this study is secondary data in the form of company financial statements from 2017 to 2021. The method of analysis in this research is descriptive quantitative using analysis of the ratio of Return on Investment and Residual Income ratio. The results showed that the value of Return on Investment PT. Biringkassi Raya from 2017 to 2021 has fluctuated and has not been effective because it is below industry standards, this is because the company's revenues and assets have decreased so that the company's profits have also decreased. While the Residual Income value also shows an unfavorable condition, this is because the Residual Income value has decreased from year to year.